Impact of Leadership, Organizational Culture and Communication System on Human Capital and Implication on Productivity Enhancement in Indonesian Public Sector - Rini Mulyani Sari; Evan Nugraha (Technium Social Sciences Journal, 2020)
The rationale of this have a see at was to decide the association between authority, organizational culture and communication framework on human capital execution and suggestion on efficiency upgrade at the Secretariat of the Regional People’s Representative Council. The approach utilized is quantitative the utilize of way examination strategy. The amount of respondents is 102 people who are workers of the Secretariat of the Regional People’s Representative Council. The see at was carried out starting from checking out considers contraptions, checking out theories both for halfway connections, synchronous connections and coefficient of determination, at that point the remaining degree changed into inspected for the achievability of a considers show based completely on a few measures, particularly: hypothetical plausibility, exactness of estimation of the parameters, informative capability and estimating capacity. From the examination results, it is discovered that leadership (X1), organizational culture (X2) and communication system (X3), human capital (Y) and productivity (Z) have a huge impact.